Explaining the Mediating Role of Emotional Processing in the Relationship Between Mindfulness and Aggression Among Adolescent Girls in Babol - Safarzadeh, Fatemeh; Sadeghi, Jamal; Ahmad Khosravi, Saeed; Aghajani Hashtjin, Tahmorash (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to examine the mediating role of emotional processing in the relationship between mindfulness and aggression among female adolescents in the second cycle of secondary education. Methods and Materials: This study employed a basic, cross-sectional design using a descriptive–correlational approach based on covariance-based structural equation modeling (CBSEM). The statistical population consisted of all female students in the second cycle of secondary education in Babol (N = 3,343), from whom 360 participants were selected using multi-stage cluster random sampling; after excluding incomplete questionnaires, 351 cases were included in the final analysis. Data were collected using the Buss–Perry Aggression Questionnaire (Buss & Perry, 1992), the Emotional Processing Scale (Baker et al., 2010), and the Kentucky Inventory of Mindfulness Skills (Baer et al., 2004). Data were analyzed using SPSS version 27 and AMOS version 24 at a significance level of .05. Assumptions of normality, absence of multicollinearity, and independence of errors were examined prior to model testing. Findings: Structural equation modeling indicated that mindfulness had a direct, negative, and statistically significant effect on aggression (β = -0.34, p < .01). Mindfulness also showed a significant negative direct effect on maladaptive emotional processing (β = -0.48, p < .01). Emotional processing demonstrated a direct, positive, and statistically significant effect on aggression (β = 0.37, p < .01). Furthermore, the indirect effect analysis revealed that mindfulness significantly reduced aggression through its impact on emotional processing (β = -0.18, p < .01), confirming the mediating role of emotional processing in the structural model. Conclusion: The findings suggest that mindfulness reduces aggressive behavior among female adolescents both directly and indirectly through improving emotional processing. Enhancing mindfulness skills may therefore contribute to healthier emotional integration and decreased aggression during adolescence, highlighting the importance of incorporating mindfulness-based interventions within school-based prevention and mental health programs.